2013
DOI: 10.7554/elife.01197
|View full text |Cite
|
Sign up to set email alerts
|

Bone morphogenic protein signalling suppresses differentiation of pluripotent cells by maintaining expression of E-Cadherin

Abstract: Bone morphogenic protein (BMP) signalling contributes towards maintenance of pluripotency and favours mesodermal over neural fates upon differentiation, but the mechanisms by which BMP controls differentiation are not well understood. We report that BMP regulates differentiation by blocking downregulation of Cdh1, an event that accompanies the earliest stages of neural and mesodermal differentiation. We find that loss of Cdh1 is a limiting requirement for differentiation of pluripotent cells, and that experime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
91
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(104 citation statements)
references
References 59 publications
13
91
0
Order By: Relevance
“…Thus, it appears that silencing the Id1 gene can improve the neural differentiation rate of MSCs, consistent with a report that neural differentiation can be increased by suppressing Id1 expression in zebrafish [32]. It has been reported that high expression of Id1 promotes cell proliferation and inhibits cell differentiation [33,34], which is in agreement with the reports that overexpression of Id1 maintains the undifferentiated state by sustaining pluripotency markers [35] and preventing commitment to a neural fate [36]. The bHLH family consists of two classes of transcription regulators: inhibitors (such as Hes and Id) and activators (such as Mash1, Math1 and NeuroD).…”
Section: Neural Differentiation and Immunocytochemistrysupporting
confidence: 80%
“…Thus, it appears that silencing the Id1 gene can improve the neural differentiation rate of MSCs, consistent with a report that neural differentiation can be increased by suppressing Id1 expression in zebrafish [32]. It has been reported that high expression of Id1 promotes cell proliferation and inhibits cell differentiation [33,34], which is in agreement with the reports that overexpression of Id1 maintains the undifferentiated state by sustaining pluripotency markers [35] and preventing commitment to a neural fate [36]. The bHLH family consists of two classes of transcription regulators: inhibitors (such as Hes and Id) and activators (such as Mash1, Math1 and NeuroD).…”
Section: Neural Differentiation and Immunocytochemistrysupporting
confidence: 80%
“…In adherent culture in the absence of serum factors, ES cells progress from naïve pluripotency into a population that resembles the early post‐implantation formative epiblast 16, 45, 81, 82 with competence for germline and somatic lineage specification 17, 45, 81, 83. This process is asynchronous, with individual ES cells departing from the naïve state at different times 16, 84, 85. The findings here indicate that pERK1/2 activity is limiting for progression from the naïve state.…”
Section: Discussionmentioning
confidence: 99%
“…In this situation, BMP and Wnt/β-Catenin signalling in the context of low FGF/ERK signalling and high levels of E-Cadherin, play a pivotal role in this balance (Ying et al, 2003a; Ying et al, 2008; Wray et al, 2011; Faunes et al, 2013; Malaguti et al, 2013) and maintain the pluripotency network in a homeostatic steadiness. Triggering differentiation artificially and neutrally e.g.…”
Section: Discussionmentioning
confidence: 99%